Mamiferos - Ring, Susan (Mankato, Minn. : Yellow Umbrella Books/Capstone Press, 2005)
This book is a very simple introduction to various mammals and some of their characteristics.
Includes index.
Includes glossary.
PURCHASED WITH IMLS FUNDS 2005.
Keywords: Mammals; Spanish language materials